The advantage of MICROWAVE-heating application in pumpkin pomace processing - O. V. Perfilova; G. O. Magomedov (Новые технологии, 2019)
In canning industry blanching is mainly used for pretreatment of plant raw materials; it consists in treating the product with steam or water with a temperature of 80 to 100°C, while the duration of heating is from 5 to 15 minutes. However, when blanching fruit and vegetable raw materials, a diffusion process inevitably occurs and a part of food substances soluble in water is transferred to the heating medium. The mechanisms of the influence of the microwave field on changes in chemical composition, including antioxidant, processed fruit and vegetable raw materials have not been studied enough. The article presents the research on the use of microwave heating for the purpose of pretreatment of pumpkin marc to increase its nutritional value. To study the influence of technological factors of microwave heating on such properties of pumpkin pomace as temperature, humidity (dry matter content), total content of antioxidants (TCA) for quercetin, the latter were heated from 50 to 960С at constant power equal to 800 W. The choice of a rational mode of microwave - heating pumpkin pomace was carried out by the maximum value of the total content of antioxidants (water soluble) for quercetin, which was determined on the Color Yauza 01-AA device. As a result, a rational mode of microwave treatment of pumpkin pomace has been determined, at which the maximum increase in the total content of antioxidants is observed: power - 800 W, time - 175 s, specific work - 700 W / g s, heating temperature of pomace - 95°C. Microwave heating of pumpkin pomace allows you to increase the total content of antioxidants to a value of 155.6 mg / 100 g mw, which is on average 3 and 17% higher than that of pumpkin juice and pumpkin, respectively.